2011
DOI: 10.1590/s1808-86942011000200003
|View full text |Cite
|
Sign up to set email alerts
|

Speech perception in adolescents with pre-lingual hearing impairment with cochlear implants

Abstract: prof ound hearing loss is a disability that affects personality and when it involves teenagers before language acquisition, these bio-psychosocial conflicts can be exacerbated, requiring careful evaluation and choice of them for cochlear implant. Aim:To evaluate speech perception by adolescents with profound hearing loss, users of cochlear implants.Study Design: prospective. Materials and Methods:Twenty-five individuals with severe or profound pre-lingual hearing loss who underwent cochlear implantation during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…A study by Souza et al 18 with adolescents aged 10 to 17 years and 11 month patients with pre-lingual hearing impairment revealed that speech perception improved substantially two years after using CI, achieving high levels of vowels and sentences recognition in open and closed settings. …”
Section: Discussionmentioning
confidence: 99%
“…A study by Souza et al 18 with adolescents aged 10 to 17 years and 11 month patients with pre-lingual hearing impairment revealed that speech perception improved substantially two years after using CI, achieving high levels of vowels and sentences recognition in open and closed settings. …”
Section: Discussionmentioning
confidence: 99%
“…Hearing rehabilitation through surgery (cochlear implant) with hearing preservation in patients with hearing remains in the low frequencies becomes a new treatment option 2 , 9 , 10 , 11 .…”
Section: Discussionmentioning
confidence: 99%
“…These patients often present sloping hearing loss where low frequency thresholds (up to 1,000 Hz) are preserved and higher frequency thresholds are lower, with severe or profound hearing loss at middle and high frequencies. A new form of therapy arose as the concept of auditory preservation developed and technological advances were made in cochlear implants, namely electric acoustic or hybrid stimulation 2 , 9 , 10 , 11 , 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…De uma forma geral, a visão limitada da surdez como deficiência suscita nas famílias desafios no tocante à aceitação da surdez, à dificuldade de comunicação com os filhos, à luta contra o preconceito social existente, à resistência ao uso da língua de sinais tanto dos membros da família como da sociedade (Pereira, 2013;Santos & Molon, 2014). Um entendimento imediatista muito adotado com vista à correção da deficiência auditiva diz respeito à utilização de tecnologia cada vez mais sofisticada, como a disponibilização de aparelhos auditivos e implantes cocleares, existindo já evidências sobre a melhoria da qualidade de vida dos implantados (Souza Brito, Bento, Gomez, Tsuji, & Hausen-Pinna, 2011;Ramos, et al, 2015). O recurso aos aparatos tecnológicos para normalização da população surda gera, na família, nos profissionais de saúde e na população geral, uma expectativa de inclusão.…”
Section: Os Gestos Foram Durante Muito Tempo Proibidos Em Institutounclassified
“…A conceção de surdez como sendo deficit sensorial, visa apenas os aspetos orgânico-biológicos oriundos da filosofia oralista, que concebe os Surdos inclusos socialmente por meio de treinos intensos tanto da fala e leitura labial, como do treino auditivo na tentativa de tornar o Surdo oralizado (Nóbrega, Andrade, Pontes, Bosi & Machado, 2012). Esta é usualmente difundida através da disponibilidade de aparelhos auditivos e implante cloquear na correção auditiva, utilizada pelos serviços de saúde em resposta às políticas públicas face aos deficientes auditivos (Souza Brito, Bento, Gomez, Tsuji, & Hausen-Pinna, 2011;Ramos, Jorge, Teixeira, Ribeiro & Paiva, 2015). Contudo, apesar dos avanços tecnológicos da recuperação auditiva, há relatos de resistências ao uso destes aparatos em decorrência do desconforto causado pela interferência dos ruídos audíveis e dos sofrimentos psicológicos em consequência da imposição familiar para torná-los ouvintes (Nóbrega et al, 2012;Silva & Abreu, 2014).…”
Section: Introductionunclassified